Increasing Sensitivity of Optical Receivers using a Divide-and-Conquer Technique - Royo, Guillermo; Martínez Pérez, Antonio Dionisio; Aldea Chagoyen, Concepción; Celma Pueyo, Santiago (Jornada de Jóvenes Investigadores del I3A, 2020)
This paper presents a noise-reduction technique to increase the sensitivity of optical receivers with large integrated photodiodes (PD). It consists of manufacturing the PD in several pieces and connecting each piece to a dedicated transimpedance amplifier (TIA). The output signals are combined achieving a better sensitivity and a higher transimpedance.